The Influence of Digital Literacy on Reading Interests of Elementary School Students - Pesona Rasyidnita; Najwa Amalia Putri; Khellaviani Syifa; Destania Eka Putri; Arfian (Insight School Academy, 2024)
Introduction to The Problem: The study aims to explore the impact of digital literacy on elementary school students' reading interests, particularly focusing on the period during the Covid-19 pandemic. It highlights how digital literacy has enabled students to access a broader range of online reading materials, including textbooks and other educational resources, thereby potentially influencing their reading interests positively. Purpose: The primary purpose of this research is to understand the relationship between digital literacy and elementary school students' reading interests. It seeks to determine whether and how digital literacy skills affect students' ability to engage with and enjoy reading materials available online. Design/methods/approach: This research employs a library research approach, which involves reviewing and analyzing existing literature on the topic. It aims to gather data by studying theories and findings from various sources related to digital literacy and its effects on reading habits among elementary school students. Findings: The research concludes that digital literacy plays a significant role in enhancing elementary school students' reading interests. It finds that students with higher levels of digital literacy are better equipped to navigate and utilize online reading materials, which can contribute to increased engagement and interest in reading. Research implications/limitations: While the study provides valuable insights into the positive impact of digital literacy on reading interests, it acknowledges limitations such as the reliance on secondary data and the potential for variations in digital literacy skills among students. These factors may limit the generalizability of the findings. Originality/value: This research contributes to the growing body of knowledge on the importance of digital literacy in education by specifically examining its effect on elementary school students' reading interests. It offers practical implications for educators and policymakers looking to leverage technology to enhance student engagement with reading materials.